ANALYSIS OF ROAD SURFACE DISTRESS USING PAVEMENT CONDITION INDEX (PCI) AND BINA MARGA METHOD (Case Study: Jalan KH. Abdurahman Wahid, STA. 0+000 – STA. 1+950, Wonosobo Subdistrict) - Nugroho, Galang -; Saputra, Vian Guntur; Wardani, Agustina; Budirahardjo, Slamet (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2025)
Wonosobo is one of the tourist destinations in Central Java, making highways a vital element in supporting the mobility of both residents and visitors. One of the strategic roads is Jalan KH. Abdurahman Wahid, which connects the center of Wonosobo City with the Dieng Tourism Area. The surface condition of this road segment shows various types of damage that have the potential to disrupt transportation flow. This study aims to analyze the surface layer damage on Jalan KH. Abdurahman Wahid from STA. 0+000 to STA. 1+950 in Wonosobo District using two approaches: the Pavement Condition Index (PCI) method and the Bina Marga Method. The PCI method is used to evaluate the extent of damage based on visual inspection results, while the Bina Marga Method is employed to identify types of damage and determine their handling priority levels through the calculation of Priority Order (Urutan Prioritas/UP). The survey and analysis results indicate eight types of damage based on the Pavement Condition Index (PCI), with an average PCI score of 35.62 (categorized as Very Poor), and the lowest score of 20 (categorized as Serious) found in sample units 3, 10, and 13. According to the Bina Marga Method, six types of damage were identified with a Priority Order (UP) value of 6, indicating that the road segment falls into the priority category for Periodic Maintenance. It can be concluded that this road segment requires immediate treatment either in specific sections or along the entire stretch. The analysis results are expected to serve as a consideration for relevant agencies in managing road infrastructure effectively and sustainably.